Prevalence and pattern of congenital heart disease among children with Down syndrome seen in a Federal Medical Centre in the Niger Delta Region, Nigeria - Susan, Ujuanbi Amenawon; Chiemerie, Onyeka Adaeze (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Down syndrome (DS), or Trisomy 21, is the most common genetic disorder in the world and congenital heart disease (CHD) contributes significantly to morbidity and mortality in this population. Early diagnosis and prompt cardiac intervention improve their quality of life. This study was done to determine the prevalence and pattern of congenital heart disease among children with Down syndrome seen at the Paediatric Cardiology Unit of Federal Medical Centre (FMC), Bayelsa State. Method: A prospective study of children with Down syndrome referred for cardiac evaluation and echocardiography at the Paediatric Cardiology Unit of FMC, Bayelsa State over four years from 1st January 2016 to 30th December 2019. Data on socio-demographic information, echocardiographic diagnosis, and outcome were retrieved from the study proforma and analyzed. Results: A total of 24 children with Down syndrome were seen over the study period. Their age ranged from 0 to 16 years. The majority, 20 (83.3%) of the children with Down syndrome were aged 5 years and below. There were 13 males and 11 females with a male to female ratio of 1.2:1. A total of 23 (95.8%) of the children with Down syndrome had CHD. The most common CHD was AVSD (including complete, partial, isolated, or in association with other defects) in 66.6% followed by TOF in 8.3%. Multiple CHDs were seen in 43.5% of the children. Only one child (4.2%) had a structurally normal heart on echocardiography. All the children with Down syndrome had pericardial effusion of varying severity while 33% had pulmonary artery hypertension (PAH). The fatality rate among the children seen with Down syndrome over the study period was 34.8% and only one child (4.2%) had open-heart surgery with the total repair of cardiac defect during the study period. Conclusion: Morbidity and mortality are high among children with Down syndrome due to the high prevalence of CHD. Early referral, diagnosis, and prompt intervention are encouraged.